The Anglo-Egyptian Sudan: from collaboration mechanism to party politics, 1898-1956 - Abu Shouk, Ahmed Ibrahim (Routledge, 2010)
This article examines the features of the collaboration mechanism that permitted a handful of Anglo-Egyptian colonial officers to incorporate tribal shaykhs and educated Sudanese into the structure of the colonial regime (1898–1956) and manipulate religious leaders and merchants to function in harmony with the government's objectives. It discusses how the Khartoum policy-makers maintained a wide scope of choices in shifting their support from one client to another along the lines of their political agendas. It investigates the gradual shift from collaboration mechanism to party politics, highlighting the response of the Khartoum policy-makers and the Sudanese nationalists who were largely influenced by the divergent attitudes of London and Cairo towards the future of the Sudan, and that of Sayyid Ali al-Mirghani and Sayyid Abd al-Rahman al-Mahdi who had a widespread influence on Sudanese society. The distinctive features of the pre-independence political discourse are examined in terms of the support that the colonised (i.e. the Umma and the National Unionist parties) received from the colonisers (Britain and Egypt) in order to run their election campaigns in 1953 and pave the way for post-independence political roles. Thus, the collaborative relationship between the colonisers and colonised reflects the uniqueness of the case of the Anglo-Egyptian Sudan in the history of British colonialism in Africa and the drive of African nationalists towards decolonisation